2084 : artificial intelligence and the future of humanity - Lennox, John C., 1943- (Grand Rapids, MI. Zondervan Reflective, 2020)
What will the year 2084 hold for you--for your friends, for your family, and for our society? Are we doomed to the grim dystopia imagined in George Orwell's 1984? In 2084, scientist and philosopher John Lennox will introduce you to a kaleidoscope of ideas: the key developments in technological enhancement, bioengineering, and, in particular, artificial intelligence. You will discover the current capacity of AI, its advantages and disadvantages, the facts and the fiction, as well as potential future implications. The questions posed by AI are open to all of us. And they demand answers. From back cover
Includes bibliographic references and indexes
Keywords: Orwell, George, -- 1903-1950.; Information technology -- Religious aspects; Artificial intelligence -- Religious aspects; Forecasting -- Religious aspects; Eschatology